HEAVY METAL CONCENTRATIONS IN WATER , Clarias gariepinus and Tilapia guineensis FROM AGODI LAKE IN IBADAN (2012)
The presence of heavy metals in food remains an issue of public health concern. At low concentrations above threshold limit, they are poisonous and can lead to toxicity in humans. Several studies have assessed heavy metals concentration in water and fish from different lakes but there is paucity of information on Agodi lake in Ibadan, a recipient of treated effluent from the sewage treatment facility of the University College Hospital (UCH) and also a source of drinking water and fish for human consumption. The study was therefore designed to assess the concentration of heavy metals in water and two fish species (Clarias gariepinus and Tilapia guineensis) from the lake. A laboratory based study was adopted. Fish and water samples were collected weekly at different locations from Agodi lake for four consecutive weeks between June and July, 2009 and analysed for physicochemical parameters using the American Public Health Association (APHA) standard method. The parameters included, pH, dissolved oxygen (DO), lead, cadmium, chromium, zinc and copper. At each sampling, six fish were randomly collected per specie. The body weight and length of each sample were measured, dissected and liver, gill, skin and muscle tissues were removed for analysis. The tissue samples were oven dried at 110 0C and homogenised. The homogenised tissue samples were acid digested and analysed for heavy metals using Atomic Absorption Spectrophotometer. Results obtained for heavy metal concentration were compared with National Guideline Limits (NGL), Standard Organisation of Nigeria (SON) and World Health Organisation (WHO) guideline limits. Descriptive statistics, t-test and ANOVA were used for the data analysis. The mean pH and DO levels in water were 7.20 ± 0.31 and 4.39 ± 2.08 mg/L respectively. The mean concentrations (mg/L) of heavy metals in water were: 0.01±0.01 (cadmium) ; 0.01 ± 0.01 (chromium); 0.02 ± 0.01 (copper); 0.04±0.01 (zinc); 0.06±0.04 (lead). These were within SON and WHO permissible limit except Lead (Pb) which was above 0.01 mg/L and 0.05 mg/L limits respectively. The heavy metal with the highest concentration found in both fish species was Zinc and the one with the least concentration was Cadmium. The mean concentrations (mg/kg) of heavy metals in cat fish were, 0.73±0.25 (cadmium) ; 4.8 ± 0.34 (chromium) ; 7.51±1.8 (lead) ; 17.62±0.27 (copper) ; 119.22±0.51 (zinc) while those of tilapia fish were, 0.48 ±0.22 (cadmium); 3.57±1.13 (chromium); 7.91 ± 1.69 (lead); 17.37±0.34 (copper) ; 176.82±0.27 (zinc). All heavy metals assessed in fish were above WHO and National guideline limits. There was no significant difference in concentrations among heavy metals within each fish specie and no significant difference in heavy metals between species except zinc ( p<0.05). The release of heavy metals into Agodi lake has increased the risk of its use as source of water for human activities and the consumption of resident fin-fishes. The need for adoption and enforcement of appropriate monitoring and management strategies for the protection of the lake is therefore important.